Comprehensive Geriatric Assessment: Application and correlations in a real-life cross-sectional study - Salis, Francesco; Loddo, Simona; Zanda, Francesca; Peralta, Maria Monica; Serchisu, Luca; Mandas, Antonella (Frontiers in Medicine, 2022)
- BACKGROUND The assessment process of elderly people takes into account all aspects of an individual’s life, including physical, mental, and social aspects. Frailty refers to a decline in physiological functions or strength leading to increased vulnerability to stressors and decreased ability to cope with them. Comprehensive Geriatric Assessment (CGA) is a validated and useful tool in this context to holistically study elderly people. The primary aim of this study was to examine the performance status presented by geriatric patients turning to outpatient service, based on components of the CGA, and thus to describe its usefulness in real-life clinical practice. The secondary aim of this study was the evaluation of the impact of the nutritional status, assessed with Mini Nutritional Assessment (MNA) – within the CGA – on cognitive-affective and functional capacities, and multimorbidity. - METHODS This real-life, retrospective cross-sectional study included subjects consecutively evaluated from January 2009 to December 2020 at the Geriatric Outpatient Service, University Hospital of Monserrato, Cagliari, Italy. A sum of 3260 patients were subjected to CGA. - RESULTS Only a small proportion of the sample (2.24%) showed absence of impairment in cognitive-affective, functional, and nutritional domains. Moderate correlations were found between MNA and several other CGA variables: Geriatric Depression Scale (ϱ=-0.41, p<0.0001), Barthel Index of Independence in Activities of Daily Living – ADL (ϱ=0.51, p<0.0001), Instrumental Activities of Daily Living – IADL (ϱ=0.43, p<0.0001), Performance-Oriented Mobility Assessment (ϱ=0.44, p<0.0001). A multiple regression also highlighted these variables as significant regressors of MNA. Finally, malnutrition showed a significant association with depression (OR: 4.97), dependence in ADL (OR: 19.8) and IADL (OR: 7.04), and falling risk (OR: 5.16). - CONCLUSION Our study has figured out the complex situation in which geriatric care finds itself : the complexity and severe impairment of elderly people. The possibilities of intervention are often limited, but the literature confirms the benefits of good nutritional status on the general health status. The data emerged from our study fit into this assumption, highlighting the close association between the nutritional domain and the other CGA domains.